2023
DOI: 10.1021/acs.est.2c05911
|View full text |Cite
|
Sign up to set email alerts
|

Exposures to Organophosphate Esters and Respiratory Morbidity among School-Aged Children with Asthma

Abstract: Organophosphate esters (OPEs) are an emerging class of chemicals used in a variety of consumer products as flame retardants, plasticizers, and additives. While prior epidemiologic studies suggest that OPEs may impact respiratory health, results remain inconclusive. We examined associations between urinary biomarkers of OPEs and symptoms of respiratory morbidity in a panel study of 147 predominantly Black school-aged children with asthma living in Baltimore City, Maryland. The study consisted of up to four seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Despite this, our research goal was clearly accomplished by demonstrating a significant increase in human exposure to OPEs through SHLBs. Newly published studies have suggested that OPE exposure may contribute to or be associated with thyroid function alterations and thyroid cancer occurrence, increase the odds of daytime asthma symptoms in school-aged children, negatively affect female reproduction, and elevate the risk of type 2 diabetes in older adults . Therefore, the SHLB, which was verified as a non-negligible OPE exposure pathway, should be given particular attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, our research goal was clearly accomplished by demonstrating a significant increase in human exposure to OPEs through SHLBs. Newly published studies have suggested that OPE exposure may contribute to or be associated with thyroid function alterations and thyroid cancer occurrence, increase the odds of daytime asthma symptoms in school-aged children, negatively affect female reproduction, and elevate the risk of type 2 diabetes in older adults . Therefore, the SHLB, which was verified as a non-negligible OPE exposure pathway, should be given particular attention.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their physical mixing rather than chemical bonding with industrial materials, OPEs can easily leach into the surrounding environment. , Ubiquitous occurrences of OPEs have been identified in air, drinking water, indoor and outdoor dust, , living environments, and global foodstuffs, , all of which are important exposure pathways of humans. Recent studies have indicated potential adverse effects of OPEs on humans, including but not limited to hepatotoxicity, neurotoxicity, endocrine disruption, reproductive toxicity, and developmental toxicity. The evidence has drawn significant public attention due to both OPEs’ abundant presence and their potential impact on human health.…”
Section: Introductionmentioning
confidence: 99%